Healthcare-Associated Infections After Aneurysmal Subarachnoid Hemorrhage: A Retrospective Single-Center Cohort Study - Aleksandra Kosikowska; Aleksandra Tołkacz; Zuzanna Nowak; Adrianna Lebiedzińska; Jarosław Kędziora; Waldemar Goździk; Jowita Woźniak; Małgorzata Burzyńska (Journal of Clinical Medicine, 2026)
Background/Objectives: Healthcare-associated infections (HAIs) frequently complicate aneurysmal subarachnoid hemorrhage (aSAH) requiring neurocritical care. We assessed their incidence, timing, microbiology, associated factors, and outcomes. Methods: This retrospective, single-center cohort study included 106 consecutive adults with acute aSAH admitted to a neurocritical care unit during 2019–2024. Time to first HAI was analyzed using cause-specific Cox regression with competing risks; to limit immortal-time bias, HAI was modeled as a time-dependent exposure in outcome analyses. Results: HAIs occurred in 47 patients (44.3%; 95% CI 35.2–53.8); median onset was 10 days (IQR 8–12). Seventy-six episodes were recorded; site-specific figures denote affected patients, with no recurrent same-site episodes: ventilator-associated pneumonia, 30 (28.3%); catheter-associated urinary tract infection, 24 (22.6%); cerebrospinal fluid infections, 13 (12.3%); and central line-associated bloodstream infection, 9 (8.5%). Acinetobacter baumannii predominated, accounting for all extensively drug-resistant isolates. High World Federation of Neurosurgical Societies grade was associated with the first HAI (HR 4.168; 95% CI 2.072–8.384), as was higher modified Fisher grade in sensitivity analysis (HR 2.886; 95% CI 1.237–6.735). Time-dependent HAI was associated with a lower hazard of live discharge (HR 0.295; 95% CI 0.164–0.529) but not with in-hospital mortality (HR 1.178; 95% CI 0.478–2.902). Its association with the discharge Glasgow Outcome Scale (GOS) was threshold-dependent (GOS ≤ 1: OR 0.715, 95% CI 0.264–1.933; GOS ≤ 3: OR 7.939, 95% CI 2.580–24.436). Conclusions: HAIs affected nearly half of this cohort. Greater initial severity was associated with a higher hazard of first HAI; HAI, in turn, was associated with prolonged hospitalization and unfavorable functional outcome, but not with mortality. These associations are observational, not causal. Surveillance, timely diagnosis, and infection prevention remain integral to neurocritical care in aSAH.